Trajectory Following Method on Output Regulation of Affine Nonlinear Control Systems with Relative Degree not Well Defined - Janson Naiborhu (Journal of Mathematical and Fundamental Sciences, 2011)
The problem of output regulation of affine nonlinear systems with the relative degree not well defined by modified steepest descent control is studied. The modified steepest descent control is a dynamic feedback control which is generated by the trajectory following method. By assuming the system is minimum phase, output of the system can be regulated globally asymptotically.